Evaluasi Program Pemberian Bantuan Pupuk untuk Meningkatkan Produksi Bagi Petani Kelapa Sawit di Kecamatan Pangkalan Kuras Kabupaten Pelalawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the fertilizer assistance policy for oil palm farmers in Pangkalan Kuras District, Pelalawan Regency, focusing on its effectiveness, targeting accuracy, and impact on production improvement. The research employed a descriptive qualitative approach using in-depth interviews, field observations, and documentation as data collection techniques. The findings indicate that although the program is intended to enhance oil palm productivity, its implementation faces several challenges such as delayed fertilizer distribution, inaccurate targeting of beneficiaries, and lack of technical assistance. Most farmers reported that fertilizers often arrive after the ideal planting season and are not distributed evenly. Additionally, the absence of accurate farmer data systems has led to unfair distribution and vulnerability to misuse. This study recommends improvements in the distribution mechanism, digital-based data updating for recipients, and the strengthening of farmer institutions and continuous extension services to ensure the program is more effective and impactful. A comprehensive policy evaluation is expected to ensure that fertilizer assistance truly contributes to increasing yields and promoting the sustainable welfare of oil palm farmers.